2015
DOI: 10.1016/j.joca.2015.05.033
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced CT facilitates rapid, non-destructive assessment of cartilage and bone properties of the human metacarpal

Abstract: Objective The aim of this work is to establish the human metacarpal as a new whole joint surface early-stage osteoarthritis (OA) model that enables comparisons of articular cartilage and subchondral bone through high resolution contrast-enhanced CT (CECT) imaging, mechanical testing, and biochemical analysis. Design The 4th metacarpal was obtained from 12 human cadaveric donors and baseline μCT imaging was followed by indentation testing. The samples were then immersed in anionic (Ioxaglate) and cationic (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
56
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(66 citation statements)
references
References 44 publications
(72 reference statements)
9
56
1
Order By: Relevance
“…Successful application of these cationic contrast agents in ex vivo and in vivo studies [7,8] indicate significant research potential. The distribution of CA4+ in AC is based on the attraction between the positive CA4+ and the negatively charged GAG macromolecules [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Successful application of these cationic contrast agents in ex vivo and in vivo studies [7,8] indicate significant research potential. The distribution of CA4+ in AC is based on the attraction between the positive CA4+ and the negatively charged GAG macromolecules [5].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, we hypothesize that cationic CA4+ will accumulate in the chondrons or in the close proximity of the chondrons. However, the previous studies using CA4+ enhanced micro-computed tomography (µCT) [5][6][7][8][9] have been conducted with insufficient resolution to answer this hypothesis. The insufficient resolution has also prevented to answer the question whether CA4+ accumulation in chondrons could lead to an erroneous quantification of GAG distribution with low resolution µCT setups.…”
Section: Introductionmentioning
confidence: 99%
“…Contrast‐enhanced computed tomography (CECT) enables detection of changes in cartilage composition along with quantitative evaluation of subchondral bone density and structure . Advantages of CECT compared with MRI are shorter acquisition times, higher resolution, and lower costs.…”
mentioning
confidence: 99%
“…Mean cartilage thickness was measured (analyze) from the baseline scan at the central apex of the hemispherical cartilage surface prior to indentation testing. The indentation equilibrium modulus ( E ) of each sample was evaluated using a standard, four‐step indentation testing procedure (see Supplementary Information, SI) …”
Section: Methodsmentioning
confidence: 99%
“…For the equilibrium study, samples were imaged in the air after a 24‐h immersion, as this was found to be sufficiently beyond the equilibrium immersion time from the diffusion‐in data. The data were converted to DICOM format (Scanco Medical) before post‐processing analysis (Analyze™; AnalyzeDirect, Overland Park, KS) …”
Section: Methodsmentioning
confidence: 99%